2022
DOI: 10.1002/ctm2.761
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase Smyd2 contributes to blood‐brain barrier breakdown in stroke

Abstract: Background The blood‐brain barrier (BBB) plays a principal role in the healthy and diseased central nervous systems, and BBB disruption after ischaemic stroke is responsible for increased mortality. Smyd2, a member of the SMYD‐methyltransferase family, plays a vital role in disease by methylation of diverse substrates; however, little is known about its role in the pathophysiology of the brain in response to ischaemia‐reperfusion injury. Methods Using oxygen glucose deprivation and reoxygenation (OGD/R)‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…93 The protein methyltransferase SET and MYND domain-containing protein 2 (SMYD2) histone methyltransferase that methylates H3K4 or H3K36 was shown to increase in the cortical peri-infarct region and SMYD2 knockout reduced BBB breakdown, edema, neurological deficits, and secondary brain damage following transient MCAO in mice. 94 In vitro analysis of primary rat brain microvascular endothelial cells showed that SMYD2 regulates the sphingosine kinases involved in endothelial cell barrier integrity via methylation-mediated ubiquitin-dependent degradation after OGD, indicating that SMYD2 potentiates post-ischemic BBB disruption. 94 In the astrocytes of middle-aged female mice, H3K4 histone methyltransferase activity was decreased compared to adult female mice following transient MCAO.…”
Section: Stroke and Histone Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…93 The protein methyltransferase SET and MYND domain-containing protein 2 (SMYD2) histone methyltransferase that methylates H3K4 or H3K36 was shown to increase in the cortical peri-infarct region and SMYD2 knockout reduced BBB breakdown, edema, neurological deficits, and secondary brain damage following transient MCAO in mice. 94 In vitro analysis of primary rat brain microvascular endothelial cells showed that SMYD2 regulates the sphingosine kinases involved in endothelial cell barrier integrity via methylation-mediated ubiquitin-dependent degradation after OGD, indicating that SMYD2 potentiates post-ischemic BBB disruption. 94 In the astrocytes of middle-aged female mice, H3K4 histone methyltransferase activity was decreased compared to adult female mice following transient MCAO.…”
Section: Stroke and Histone Methylationmentioning
confidence: 99%
“…94 In vitro analysis of primary rat brain microvascular endothelial cells showed that SMYD2 regulates the sphingosine kinases involved in endothelial cell barrier integrity via methylation-mediated ubiquitin-dependent degradation after OGD, indicating that SMYD2 potentiates post-ischemic BBB disruption. 94 In the astrocytes of middle-aged female mice, H3K4 histone methyltransferase activity was decreased compared to adult female mice following transient MCAO. 30 Concomitantly, adult female mice displayed higher enrichment of H3K4me3 (transcriptional enhancer) versus H3K9me3 (transcriptional repressor) compared to middle-aged mice, indicating less active chromatin in the astrocytes of aged females after stroke.…”
Section: Stroke and Histone Methylationmentioning
confidence: 99%
“…The other isoform, Sphk2, is necessary to regulate junctional protein expression and BBB protection in hypoxic preconditioning-induced cerebral ischemic tolerance in rats [ 213 ]. The histone methyltransferase Smyd2-dependent methylation of the Sphk/S1PR signaling pathway produces BBB disruption in experimental ischemic stroke in rats [ 214 ]. The preservation of S1P levels produced by the downregulation of SGPL1 enhances barrier function in human cerebral microvascular endothelial cells following an inflammatory challenge [ 178 ].…”
Section: S1p Signaling In Blood–brain and Intestinal Barrier Functionsmentioning
confidence: 99%
“…Many studies have shown that oxidized low-density lipoprotein (ox-LDL)-associated brain microvascular endothelial cell injury is strongly related to the progression of atherosclerotic cerebrovascular diseases. 1,2 Therefore, elucidating the molecular mechanism of ox-LDL-induced brain microvascular endothelial cell injury is of great significance for alleviating cerebrovascular atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%